Potensi Pembayaran Jasa Lingkungan Hutan Mangrove di Kecamatan Jailolo Kabupaten Halmahera Barat - Sukarmin Idrus; Ahyar Ismail; Meti Ekayani (Jurnal Ilmu Pertanian Indonesia, 2016)
Payment for environmental services (PES) to mangrove forest is judged appropriate for applied in Jailolo Sub-district of West Halmahera District as a protection of mangrove ecosystems. This is due to the high utilization of mangrove environment services. If not managed properly can potentially threaten the preservation of mangrove forests. Benefits that have been perceived by the public such as a water source, pond, travel, as well as the protection of coastal areas. These benefits must be preserved for the future availability of environmental services namely through the payment of the services already provided the commonly named as payment for environmental services (PES). PES is also very supported by West Halmahera District Regulation No. 4 of 2012 year and constitution No. 32 of 2009 year about the protection and environmental management. Basically, PES is a scheme that aims to restore and protect the availability of goods and environmental services sustainable. Therefore, PES initiation for mangrove forest economy preservation in Jailolo Sub-district needs to be studied. This research aims to: 1) Identify environmental services of mangrove forest ecosystems that are potential for PES; 2) Examines the perceptions of the public service providers (providers) towards the implementation of the plan; and 3) How much willingness to accept (WTA) community as a providers of environmental services (providers) if PES is applied. The research results showed that the service potentially initiated PES are sea-water intrusion regulating service and the cultural service of mangrove tourism. For perception and public participation, environmental service providers about the mangrove environment services were judged to be sufficient for determining PES plan assignment, where communities want to participate if the maintenance costs were IDR3.350,00/trees/year